2018
DOI: 10.1002/hbm.24382
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of brain functional stream architecture in athletes with fast demands of sensorimotor integration

Abstract: Training‐induced neuroplasticity has been described in athletes' population. However, it remains largely unknown how regular training and sports proficiency modifies neuronal circuits in the human brain. In this study, we used voxel‐based morphometry and stepwise functional connectivity (SFC) analyses to uncover connectivity changes in the functional stream architecture in student‐athletes at early stages of sensorimotor skill training. Thirty‐two second‐year student‐athletes whose major was little‐ball sports… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 54 publications
(116 reference statements)
1
21
0
Order By: Relevance
“…In addition, similar results are found in elite karate players, suggesting brain areas associated with movement planning and visual perception having increased connectivity (Duru and Balcioglu, 2018). Our recent study using seed-based stepwise FC showed that fast-ball athletes were reported with a significantly smaller optimal connectivity distance from seed regions to the dorsal attention network (DAN) and larger optimal connectivity distance to the default mode network (DMN; Gao et al, 2019). Given the evidences above, changes in resting-state-FC brain plasticity occur in different brain areas across various sport events.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…In addition, similar results are found in elite karate players, suggesting brain areas associated with movement planning and visual perception having increased connectivity (Duru and Balcioglu, 2018). Our recent study using seed-based stepwise FC showed that fast-ball athletes were reported with a significantly smaller optimal connectivity distance from seed regions to the dorsal attention network (DAN) and larger optimal connectivity distance to the default mode network (DMN; Gao et al, 2019). Given the evidences above, changes in resting-state-FC brain plasticity occur in different brain areas across various sport events.…”
Section: Introductionsupporting
confidence: 62%
“…However, it is largely unknown how brain functions change in the process of motor training (Lappi, 2015). Some researchers attempted to investigate the difference in brain activity between athletes and non-athlete controls (NC) during certain tasks (Gao et al, 2019), with different regions of task-induced activation between the two groups that are being reported. For instance, in the visual smooth pursuit task, football players showed greater activation in the oculomotor region of the cerebellar vermis and areas of the frontal eye fields than NC, suggesting visual motor skill is required for elite football players to successfully execute complex movement during games (Kellar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attentional function includes three basic components: alertness, orientation and executive control. Alertness, orientation, and executive function were defined quantitatively by the following formula: mean RT no−cue –mean RT double−cue , mean RT center−cue –mean RT spatial−cue , RT incongruent –RT congruent ( 24 ).…”
Section: Methodsmentioning
confidence: 99%